2023
DOI: 10.1002/smll.202300003
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Photocatalytic System Designed by Spatially Separated Cocatalysts on Z‐scheme Heterojunction with Identified Charge‐transfer Processes for Boosting Removal of U(VI)

Abstract: Scheme 1. a) Natural photosynthesis and b) a biomimetic analogy used in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…As shown in Figure a, OVs-BiOBr-30 can remove about 90% of U(VI) in 60 min without the addition of any trapping agent. When (NH 4 ) 2 C 2 O 4 and TBA were used as the trapping agents for h + and • OH, the removal rate did not decrease significantly, suggesting that when h + and • OH are consumed, the rate of photogenerated electron–hole complexation is reduced, which improves the separation efficiency of photogenerated carriers . Notably, the reduction efficiency was significantly reduced to about 20% in the presence of e – and • O 2 – capture agents, suggesting that both were involved in the reduction of uranium by OVs-BiOBr-30.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure a, OVs-BiOBr-30 can remove about 90% of U(VI) in 60 min without the addition of any trapping agent. When (NH 4 ) 2 C 2 O 4 and TBA were used as the trapping agents for h + and • OH, the removal rate did not decrease significantly, suggesting that when h + and • OH are consumed, the rate of photogenerated electron–hole complexation is reduced, which improves the separation efficiency of photogenerated carriers . Notably, the reduction efficiency was significantly reduced to about 20% in the presence of e – and • O 2 – capture agents, suggesting that both were involved in the reduction of uranium by OVs-BiOBr-30.…”
Section: Resultsmentioning
confidence: 99%
“…When (NH 4 ) 2 C 2 O 4 and TBA were used as the trapping agents for h + and • OH, the removal rate did not decrease significantly, suggesting that when h + and • OH are consumed, the rate of photogenerated electron−hole complexation is reduced, which improves the separation efficiency of photogenerated carriers. 14 Notably, the reduction efficiency was significantly reduced to about 20% in the presence of e − and • O 2 − capture agents, suggesting that both were involved in the reduction of uranium by OVs-BiOBr-30. The experimental results indicate that e − and • O 2 − are the main active species and play a crucial role in the piezoelectric−photocatalytic process.…”
Section: Mechanism Of the Piezoelectric−photocatalytic Reduction Of U...mentioning
confidence: 96%
“…2b, the peaks located at ∼779.5 eV and ∼794.5 eV are ascribed to the Co-P bond in the CoP crystalline phase and the peaks at ∼782.2 eV and ∼797.6 eV are associated with the Co-O bond originating from the surface oxidation of CoP; the other two peaks correspond to Co satellite peaks. 19,[25][26][27] In Fig. 2c, the Fe 2p spectrum of Ni/Fe-P/CC displays peaks at 712.14 eV, 716.04 eV and 724.73…”
Section: Papermentioning
confidence: 98%
“…Surprisingly, the substrate benzylamine is almost completely converted to N-benzyl-1-phenylmethanimine (1 c), which proves that superoxide radicals are necessary for the dehydrogenation of intermediate phenylmethanimine. Then, in order to test the effect of acidic oxygen vacancies on the surface of the catalyst, vacancy trappers KI [61] and NaHCO 3 [62] were put into the catalyse system, and it was found that the reaction almost stopped completely. This shows that the acid oxygen vacancies on the surface of the catalyst is an indispensable factor for the reaction.…”
Section: Exploring the Mechanism Of The Dehydrogenation Of Amines Cat...mentioning
confidence: 99%